(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2022)
This work aims to reflect upon the debate over the Promotion of Healthy Nutrition legislation Nº 27642/2021, better known as frontal labeling legislation. Through a critical reflexive methodology, the potential value of the legislation is presented, as a contribution to overcome the fragmentation of the food safety regulation. First, the notion of regulatory fragmentation is explained. This notion is taken as prior assumption and analysis key. Second, the main pillars of this legislation are presented, as well as their contribution to the advance in the human right to food. Legislation 27642 is located precisely in the intersection of the sub-sectors that the regulation is fragmented. It is a first attempt of a normative and inter-institutional dialogue. Then, two appreciations on the value of the law´s legislative debate are presented: the democratization of the food lawmaking process, and the advice on some critical points in the food law institutional design. Finally, some challenges that the legislation could face during the regulation process, are presented.